'Playing favourites': Is there bias during patient selection by registrars in an Australian paediatric emergency department?. (22nd July 2014) - Ranaweera, Jeevani; Craig, Simon
<x xml:space="preserve">Abstract</x> Aim Overseas studies have suggested a bias in emergency department patient selection between paediatric and emergency medicine trainees. This study aimed to detect whether a similar bias existed in an Australasian setting. Specifically, we sought to determine whether vocational trainees choose patients based on presenting complaint, triage category or patient age. Methods A retrospective review of patients attending the Monash Medical Centre Paediatric Emergency Department (PED) was conducted during four consecutive registrar rotations from July 2010 to March 2011. A 2‐week period during the middle of each term was chosen, and data were collected from times when both emergency and paediatric registrars were present in the department. Results A total of 1222 patient records were reviewed. Emergency registrars saw 278 patients, and paediatric registrars saw 413 patients. Of those seen by emergency registrars, 62.9% had medical diagnoses, and 37.1% had non‐medical diagnoses; 14.4% were triaged as high acuity, and 85.6% were low acuity. Of those seen by paediatric registrars, 70% had medical diagnoses, and 30% had non‐medical diagnoses, while 15.9% were high acuity, and 84.1% were low acuity. Emergency registrars saw 2.5% neonates, 6.5% adolescents. Paediatric registrars saw 3.6% neonates and 6.1% adolescents. There was no significant difference between paediatric and emergency registrars in selecting patients. Conclusions Bias does not appear to exist in the selection of patients in this Australasian PED. Further study should address the impact of unbiased patient selection on emergency department efficiency and trainee education.